Umpasa and Umpama in Batak Toba Culture as A Means of Catechism in Medan Catholic Churches - Lumban Tobing, Ona Sastri (Pascasarjana IAIN Pontianak, 2023)
This article explores Umpasa and umpama of Batak Toba culture as a means of catechesim within Chatolic curches. The work uses qualitative methods with observation, interview and documentation. Descriptive analysis technique is employed based on the triangulation results of techniques and sources. The study targeted 20 adults, 3 Batak Toba cultural practitioners, and 2 priests and bishops who were on the island of Samosir Lake Toba. The work suggests that churches that live and develop today are based on tradition. Tradition is meant to include everything (such as customs, beliefs, habits, teachings, and so on) that is downwardly inhereited. One of the traditions of Batak Toba that is still preserved to this day is umpasa and umpama. This tradition is considered wise because it is used for prayers, petitioning God, and giving advices. Umpasa or umpa has always been used in the teaching of the Medan Catholic Church to the community of Batak Toba in Samosir and its surroundings and has truly become a model of church catechesis, not only by the society of Batak Toba but also as a model for catechism. The work is based on church studies within the Archdiocese of Medan.